Konsep Al-Aṣīl Wa Al-Dakhīl Perspektif Al-Suyūṭī: Studi Analisis Kitab Al-Itqān Fī Ulūm Al-Qur'ān dan Relevansinya terhadap Kritik Tafsir Kontemporer di Indonesia - Moch. Bachtiar Lutfianto (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study challenges the common assumption that the theoretical framework of al-aṣīl (authentic) and al-dakhīl (spurious) in Qur'anic exegesis is a purely contemporary invention pioneered by Ibrāhīm Khalīfah in the 1980s. By conducting a critical analysis of Jalāl al-Dīn al-Suyūṭī's (d. 1505 CE) magnum opus, al-Itqān fī Ulūm al-Qur'ān, this research demonstrates that the core elements of this framework were systematically articulated centuries earlier. Using a qualitative, descriptive-analytical approach to this library-based study, the research identifies four key components of al-aṣīl wa al-dakhīl within al-Suyūṭī's work. First, al-aṣīl encompasses interpretations grounded in linguistic sciences (naḥw, ṣarf, bayān), jurisprudence (uṣūl al-fiqh), and canonical readings (qirā'āt), alongside valid chains of transmission from the Prophet, Companions, and their successors. Second, al-dakhīl bi al-ma'thūr includes anomalous (shādhdh) and fabricated (mawḍū') traditions. Third, al-dakhīl bi al-ra'y comprises exegetical ijtihād serving sectarian interests or purely literalist readings that ignore contextual considerations. Fourth, al-dakhīl bi al-ishārah involves Sufi interpretations contradicting the Qur'an and Sunnah or those produced by unqualified exegetes. These findings position al-Suyūṭī as a significant precursor—if not a pioneer—of systematic tafsir criticism, with profound implications for evaluating contemporary Qur'anic exegesis in Indonesia's digital public sphere.